Literature Review: Pengembangan Karir Yang Efektif Di Era 4.0 - Siti In Meida Yasmin; Muhammad Risky Afandi; Aulia Rahmayanti; Mochammad Isa Anshori (Universitas 45 Surabaya, 2024)
This article was created to find out effective career development in the 4.0 era. Career planning is an important strategy for both individuals and companies. Individuals need to be proactive in planning and managing their careers, while companies need to provide support and facilities for employee career development. This era is marked by increasingly rapid technological developments and can be seen from the fact that society is tied to information technology as a basis for supporting life. This research uses library research or literature review methods. This research uses an in-depth literature review method, where various literature sources relevant to the research topic are collected and analyzed carefully. The results of the analysis and synthesis from various sources will be used to deepen understanding of the research topic and become the main basis for preparing and drawing conclusions for this journal. This research shows that career development, digital skills, and the ability to adapt to digital technology are very important to increase career success and organizations also play a role in improving the skills and abilities of their employees. In the era of Industrial Revolution 4.0, companies need to improve the skills and abilities of their employees to face increasingly fierce competition.